Food Security and Productivity: Impacts of Technology Adoption in Small Subsistence Farmers in Bolivia - Lina Salazar; Julián Aramburu; Mario González-Flores; Paul Winters (Inter-American Development Bank (IDB), 2015)
This paper presents the impact evaluation of CRIAR program, implemented in rural areas in Bolivia. The objective of CRIAR is to increase smallholders' agricultural income and food security through productivity improvements triggered by technological adoption. In this study, we use data from a sample of 1,287 households-817 beneficiaries and 470 controls- interviewed specifically for this evaluation. The econometric approach to estimate the program's impact is an instrumental variable model. This approach addresses possible endogeneity and self-selection issues that might arise from program's implementation. The results present evidence that program participation increased agricultural productivity, household income and improved food security. Overall, this study confirms the importance of considering the role of productive programs as policy tools to address vulnerability to food insecurity.
hdl:11319/6783
Keywords: O13; O33; Q12; Q16; Q18; 330; Technology Adoption; Food Security; Productivity; Instrumental Variables; Bolivia